Le système urbain tunisien. Analyse hiérarchique démo-fonctionnelle sur la base de la loi Rang-taille - Amor Belhedi (Cybergeo, 2004)
The Tunisian urban system analysis since independence in 1956 shows a primatial system where the relation between the capital city (Tunis) and second city increases despite the decrease of the urban weight of Tunis since 1956. This primarily affects some regionals cities like Sfax and Kairouan and can be explained by the regional life weakness. The analysis based on the Rank Size Rule shows that the demographic weakness is often compensate by the functional weight.